Integrating the Ethno-STEAM-Based Si PURI Worksheet to Foster Critical Thinking Skills among Fourth-Grade Elementary School Students in Indonesia - Ririn Purnawati; Suryanti Suryanti; Neni Mariana (Journal of Learning Improvement and Lesson Study, 2026)
Critical thinking skills among Indonesian elementary students remain limited, largely because contextual teaching materials integrating local wisdom are rarely available. This study developed the Si PURI worksheet through an Ethno-STEAM approach to improve fourth-grade students’ critical thinking skills. Its novelty lies in incorporating pupur, a traditional Javanese powder-based skincare practice, into a structured worksheet integrating science through the chemistry of natural ingredients, technology through processing tools, engineering through production procedures, arts through cultural aesthetics, and mathematics through measurement and proportion. This topic has not previously been explored in elementary Ethno-STEM or Ethno-STEAM worksheets. The study employed the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Participants were 23 fourth-grade students at SD Negeri 017 North Sangatta, East Kutai Regency, East Kalimantan. Data were collected through expert validation, accessibility questionnaires, and critical thinking tests administered before and after implementation. Quantitative analysis included validity and accessibility percentages, N-Gain calculations, and the Wilcoxon Signed Ranks Test. Results showed that the worksheet achieved an average validity score of 82.33%, categorized as very valid. Accessibility reached 85.62% based on evaluations from 23 students and five teachers, indicating a very good category. Effectiveness was demonstrated by an average score increase from 59.43 to 77.96, with a class N-Gain of 0.46 in the medium category. The Wilcoxon test indicated a significant difference between pretest and posttest scores (p = 0.000), while 43.5% of students reached the high improvement category. Therefore, the Si PURI worksheet is valid, accessible, and effective for fostering critical thinking skills.